Clinical, Pathological, and Molecular Characteristics in Colorectal Cancer - Dedieu, Stephane (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Despite major medical advances in recent decades, colorectal cancer remains a major public health problem with significant unmet medical needs. This reprint presents new scientific and clinical data, and discusses the need to identify new theranostic biomarkers from tissue and fluid biopsies, to go further in terms of personalised medicine and thus overcome current limitations.